Effect of maternal HIV status on vaccination coverage among sub-Saharan African children: A socio-ecological analysis - Olatunji O. Adetokunboh; Olalekan A. Uthman; Charles S. Wiysonge (Taylor & Francis Group, 2018)
We investigated the relationship between maternal HIV status and uptake of the full series of three doses of diphtheria-tetanus-pertussis containing vaccines (DTP3) in sub-Saharan African children. We used data obtained from demographic and health surveys conducted in sub-Saharan Africa. We conducted meta-analysis and calculated pooled odds ratios (OR) for the association between maternal HIV status and DTP3 vaccination status for each country. A total of 4,187 out of 5,537 children of women living with HIV received DTP3 (75.6%), compared to 71,290 of 113,513 (62.8%) children of HIV negative women. National DTP3 coverage among children of HIV-positive women varied between 24% and 96% while among children of HIV negative women it was between 26% and 92%. Overall pooled result showed no significant difference in DTP3 coverage between the two groups (OR = 1.05; 95% confidence interval 0.91 - 1.22), with statistically significant heterogeneity (Chi = 91.63, P = 0.000, I2 = 71.6%). There was no significant association between DTP3 coverage and maternal HIV status in sub-Saharan Africa. However, DTP3 coverage for both HIV-exposed and non-exposed children were below the required target. Meta-regression revealed no significant association between DTP3 coverage and country characteristics (e.g. HIV prevalence among women, antiretroviral therapy coverage, gross domestic product per capita, human development index, adult literacy rate and sub-region). Improved prevention of mother-to-child transmission services might have contributed to some extent to the higher DTP3 vaccination coverage among the HIV-exposed children. There is also need to address barriers impeding uptake of vaccination among HIV-exposed and non-exposed children.